Peran Organizational Citizenship Behavior ditinjau dari Servant Leadership dan Pemberdayaan Pada Perangkat Desa - Siti Nur Ana; Eka Askafi (Universitas Islam Kadiri, 2023)
Servant leadership and pemberdayaan impact organizational citizenship behavior in this study. This study covers all perangkat desa in Pace sub-district, Nganjuk district towns. 131 users replied 195 devices. Validity, Reliability, Classical Assumption, Multiple Linear Regression, Partial Correlation, Multiple Correlation, F, and T Tests. Research: (1) Servant leadership and Pemberdayaan significantly affect organizational citizenship behavior, with a significance value of 0.000 <0.05 and a computed F value of 281.772 > 3.066. where X1 and X2 are separate factors. (2)Servant leadership improves organizational citizenship behavior. 0.004 <0.05 and 2.914 > 1.9787. (3) Empowerment improves organizational citizenship behavior with a significance value of 0.000 <0.05 and a t count > t table of 1.9787. Researchers advise the village boss to love his officials. The village machinery will help coworkers with work issues and innovate village governance.